SOCIO-ECONOMIC APPROACH AS A PROMISING INTERVENTION TO REDUCE LEPROSY-RELATED STIGMA - Anindya Rahadyani Kristiansari (Faculty of Medicine Universitas Kristen Duta Wacana, 2019)
The context of the journal is about people with leprosy-related stigma have low self-esteem not only because their physical impacts such as deformity and the color of their skin, but also their psychological aspect like negative feeling and emotion about their body. In social aspect, they may feel rejection, discrimination, loneliness, and fear to interact with others. Further more, they may loose their job and make financial disruption. In this journal intervention research, the researchers have a goal to make a better life for people with leprosy and dissolve the stigma.